Akuntabilitas Ombudsman Republik Indonesia Perwakilan Sumatera Utara Dalam Pelayanan Publik - Murni Rahmaini; Asima Yanty Sylvania Siahaan (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The formation of the Ombudsman in Indonesia became a milestone in the start of reformation in government institution aimed at overseeing government performance. This study aims to see how the effectiveness of the Ombudsman Republic of Indonesia representative of North Sumatera in the supervision of public services. The research method used is descriptive research method with qualitative approach. Data collection techniques are done by interviewing, observing and recording documents related to supervision of public services carried out by Ombudsman Republic of Indonesia representative of North Sumatera. The data obtained are then analyzed qualitatively by reviewing all the data that has been collected supported by the results of the interview, observation. From the results of the study it can be seen that the performance of Ombudsman Republic of Indonesia representative of North Sumatera in the supervision of public services has not been effective. This is known by the number of resources both human and budget are small, limited authority of Ombudsman, the usefulness of the Ombudsman for North Sumatera, the amount of quality and output produced and the supporting facilities and infrastructure.